Tungstate-Borate Ionic Liquids: Structure, Electrochemical Behavior and Electrodeposition of Tungsten Coatings - GAB, Angelina; MALYSHEV, Victor; SHAKHNIN, Dmytro; POPESCU, Ana-Maria; CONSTANTIN, Virgil (Studia Universitatis Babeș-Bolyai Chemia, 2024)
This work was undertaken to study the electrodeposition of tungsten from the Na2WO4-B2O3 system in the molten state. The measurement of the EMF being made with platinum-oxygen indicator and tungsten relative electrodes versus platinum-oxygen. Experiment due to dependencies of the platinum-oxygen potential and tungsten electrodes on the B2O3 concentration, are validate by the forming of ditungstate ions W2O72- in the high temperature ionic liquids (HTILs).The electroreduction process of the active species, is controlled by the diffusion; the rate of formation of the active species does not limit the electrode process; Polarization, in galvanostatic and potentiodynamic mode, have highlighted the fact that charge transfer is reversible. In the Na2WO4-B2O3 melt (acid-basic character), in a narrow potential range and at a controlled process potential, the electroreduction of tungsten from its dimeric form is possible due to the multielectronic processes that take place at the electrode surface. This study played an important role in the evolution of tungsten coatings; the corrosion potentials of electrodes (copper, nickel, steel) plated with tungsten, were also measured. In this study, the influence of some parameters (temperature, electrolysis time, cathodic current density, B2O3 concentration) on the cathodic structure and composition was quantified, determining the optimal conditions of the reverse electrodeposition.